Modeling and Optimization of Adsorption and Removal of Cd(II) from Aqueous Solution by Phosphogypsum - Chafik*, D.; Bchitou, R.; Bouhaouss, A. (Asian Journal of Chemistry, 2014)
The aim of this work is the modeling and the optimization of the adsorption and the removal of cadmium by the phosphogypsum from aqueous solution. Generally, the attacks of the phosphate rock react with sulfuric acid to produce a major product phosphoric acid and phosphogypsum as a by product. This latter could be used for removing inorganic heavy metal impurities such as cadmium from aqueous solutions. We have applied two techniques for the modeling and the optimization of the removal of cadmium: First, we have used the technique of isotherms of Langmuir, Freundlich and Temkin in order to evaluate the metal quantity adsorbed. Second, we adopted the technique of Box-Behnken design experiments. The determining factors for the processes are the contact time, the concentration of Cd(II) and the phosphogypsum. The optimum concentration of Cd(II) adsorbed and phosphogypsum is 125 mg/L and 15 g/L, respectively at pH = 5, 84 and T = 22 °C.